User Satisfaction Analysis of the PT Dikstra Cipta Solusi Website Using the Webqual 4.0 Method - Hertyana, Hylenarti; Lomotu , Syahrozi; Rahmawati, Eva (Information Technology and Science (ITScience), 2024)
The abundance of IT consulting firms in this digital era necessitates continuous improvement for these companies. From services to products, everything must be constantly updated. Websites have become a crucial platform for reaching customers connected to the internet. Customer satisfaction is equally important in building trust with IT consulting firms. This makes companies more aware of the need for customer satisfaction. The Webqual 4.0 method can be a solution to help IT consulting firms understand satisfaction from the end user's perspective by measuring website quality in terms of usability, information quality, and service interaction. The use of the Webqual 4.0 method also requires IT consulting firms to pose a series of questions to existing customers to gauge how attractive, informative, useful, and secure a website is when accessed. This makes the method highly effective if the questions asked are accurate and align with the views of the customers or end users. From the research conducted on PT Diksta Cipta Solusi, it was found that the dominant characteristics of the website users are males aged 35-39 years, with a usage frequency of about twice a month. User evaluations of the website fall into the good category, with the majority of users feeling satisfied or very satisfied, as evidenced by the high validity and reliability of the assessments. The most significant factor influencing user satisfaction is usability, particularly in terms of the ease of operating the website. It was discovered that the three independent variables—usability, information quality, and service interaction—collectively influence user satisfaction. This study makes an important contribution by demonstrating the effectiveness of the Webqual 4.0 method in measuring website quality and providing insights for IT consulting firms to focus on improving usability, information quality, and service interaction to enhance user satisfaction.